2022
DOI: 10.3390/cells11091454
|View full text |Cite
|
Sign up to set email alerts
|

How CAR T Cells Breathe

Abstract: The manufacture of efficacious CAR T cells represents a major challenge in cellular therapy. An important aspect of their quality concerns energy production and consumption, known as metabolism. T cells tend to adopt diverse metabolic profiles depending on their differentiation state and their stimulation level. It is therefore expected that the introduction of a synthetic molecule such as CAR, activating endogenous signaling pathways, will affect metabolism. In addition, upon patient treatment, the tumor micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Still, to our knowledge, no optimization studies had been properly conducted on primary human CAR T cells and the increasing use of Seahorse urges for a harmonization of the Here we described the optimized conditions to evaluate the metabolism of CAR T cells using a Sea-horse XF96 analyzer. This report complements our previous review discussing Seahorse use in the context of CAR T cell studies (Forcados et al, 2022), where we noticed that although successful results were often reported (van der Windt et al, 2016;Milam et al, 2020;Mercier-Letondal et al, 2021;Kong et al, 2022), the conditions between labs dramatically varied. To our knowledge, no optimization studies had been properly conducted on primary human CAR T cells and the increasing use of Seahorse urges for a harmonization of the protocols.…”
Section: Discussionsupporting
confidence: 81%
“…Still, to our knowledge, no optimization studies had been properly conducted on primary human CAR T cells and the increasing use of Seahorse urges for a harmonization of the Here we described the optimized conditions to evaluate the metabolism of CAR T cells using a Sea-horse XF96 analyzer. This report complements our previous review discussing Seahorse use in the context of CAR T cell studies (Forcados et al, 2022), where we noticed that although successful results were often reported (van der Windt et al, 2016;Milam et al, 2020;Mercier-Letondal et al, 2021;Kong et al, 2022), the conditions between labs dramatically varied. To our knowledge, no optimization studies had been properly conducted on primary human CAR T cells and the increasing use of Seahorse urges for a harmonization of the protocols.…”
Section: Discussionsupporting
confidence: 81%
“…Memory T cells are also mostly quiescent but display a greater mitochondrial mass that provides a bioenergetic advantage to support rapid recall responses upon antigen re-exposure. Both sets of T cells rely almost completely on the energy derived from mitochondrial oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO) to maintain their basal energy level, cellular function, and viability ( 15 18 ). Following antigen exposure, T cell activation is orchestrated by TCR/peptide-MHC interaction providing the first signal forming an immune synapse.…”
Section: Brief Overview Of T Cell Metabolismmentioning
confidence: 99%
“…Further interaction at the synapse with costimulatory molecules provides the required second signal. Thus, a complete TCR-based activation of T cells requires two signals ( 15 , 19 , 20 ). Once activated, T cells predominantly engage in aerobic glycolysis, the pentose phosphate pathway (PPP), one-carbon metabolism, fatty acid oxidation (FAO), and glutaminolysis to facilitate proliferation and enable subsequent effector functions ( 17 , 21 24 ), Figure 1A .…”
Section: Brief Overview Of T Cell Metabolismmentioning
confidence: 99%
See 2 more Smart Citations